2004
DOI: 10.1103/physreve.69.051707
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous intensity dependence of optical reorientation in azo-dye-doped nematic liquid crystals

Abstract: The intensity dependence of optical nonlinearity in a nematic liquid crystal doped with an azo-dye is investigated. The reorientational part of the nonlinearity changes from self-defocusing to self-focusing character while the intensity passes through the saturation value of trans-cis photoisomerization. This observation, in accordance with previous models, indicates that the optical torque generated by the trans-isomers is of opposite sign than the torque generated by the cis-isomers. At very low intensities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…First of all, we notice that the phenomena observed for the lowmolar-mass dyes 1 0 and 2 0 are quite similar to those observed previously for azobenzene dyes [7][8][9][10][11] and can be explained by the photoconformational transitions of dye molecules. In this context, it seems possible that increasing the nonlinearity at complication of the molecular structure (passing from 1 0 to 1 and from 2 0 to 2) is due to suppression of the photoisomerization.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…First of all, we notice that the phenomena observed for the lowmolar-mass dyes 1 0 and 2 0 are quite similar to those observed previously for azobenzene dyes [7][8][9][10][11] and can be explained by the photoconformational transitions of dye molecules. In this context, it seems possible that increasing the nonlinearity at complication of the molecular structure (passing from 1 0 to 1 and from 2 0 to 2) is due to suppression of the photoisomerization.…”
Section: Discussionsupporting
confidence: 69%
“…It was found later [7][8][9][10][11] that the nonlinearity sign (the sense of the light-induced director rotation) can be different for one and the same dye. Namely, the negative nonlinearity can transform into the positive one at decreasing the angle d formed by n and the field E of the extraordinary wave (by changing the angle of light incidence on a cell or passing from the homeotropic to the planar cell) and at increasing the light intensity.…”
Section: Introductionmentioning
confidence: 99%
“…In studies of bulk reorientation, we have found that interpretation of photoinduced reorientation required the inclusion of gliding on the rubbed polyimide surface [11,12]. A drift in baseline measurements between experiments, which could not be associated with thermal drift, has also been common.…”
Section: Introductionmentioning
confidence: 91%
“…It is well known that when the number of cis isomers is increased, a corresponding reduction in the nematic order arises, eventually giving rise to isotropy [15,16]. Janossy et al [17] have shown experimentally and explained theoretically that the isomers trans and cis induced opposite light torques into a nematic matrix (E63 and Dispersed Orange 3).…”
Section: Resultsmentioning
confidence: 98%